2006
DOI: 10.1002/chin.200638073
|View full text |Cite
|
Sign up to set email alerts
|

A New Non‐Azole Inhibitor of ABA 8′‐Hydroxylase: Effect of the Hydroxyl Group Substituted for Geminal Methyl Groups in the Six‐Membered Ring.

Abstract: A New Non-Azole Inhibitor of ABA 8'-Hydroxylase: Effect of the Hydroxyl Group Substituted for Geminal Methyl Groups in the Six-Membered Ring. -Design and synthesis of inhibitor (I) are described. The (+)-enantiomer competitively inhibits 8'-hydroxylation of abscisic acid by recombinant CYP707A3. -(ARAKI, Y.; MIYAWAKI, A.; MIYASHITA, T.; MIZUTANI, M.; HIRAI, N.; TODOROKI*, Y.; Bioorg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Because the 3D structure of ABA 8'-hydroxylase has still not been investigated, we have attempted to explore the active site from the ligand side using many ABA analogues that we have developed. [19][20][21] In the process of this research, we found AHI1, a compound which can be a key molecule to uncover the mechanism of asymmetrical ligand recognition by ABA 8'-hydroxylase. AHI1 in addition to AHI1, and examined their binding potency to the ABA 8'-hydroxylase active site.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Because the 3D structure of ABA 8'-hydroxylase has still not been investigated, we have attempted to explore the active site from the ligand side using many ABA analogues that we have developed. [19][20][21] In the process of this research, we found AHI1, a compound which can be a key molecule to uncover the mechanism of asymmetrical ligand recognition by ABA 8'-hydroxylase. AHI1 in addition to AHI1, and examined their binding potency to the ABA 8'-hydroxylase active site.…”
Section: Introductionmentioning
confidence: 96%
“…[10][11][12][13] Gene knockdown and overexpression studies suggest that ABA 8'-hydroxylase is a key enzyme for controlling ABA concentration during water deficit stress or dormancy maintenance and breaking. 14,15 To chemically control ABA 8'-hydroxylation in plants, we are developing stable ABA analogues [16][17][18] and specific inhibitors [19][20][21] against ABA 8'-hydroxylase. For effectively designing these chemicals, we need to know the substrate binding and enzyme reaction mechanisms in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Although AHI4 did not exhibit ABA activity, it enhanced the effect of ABA with simultaneous treatment of both compounds in rice seedlings. Moreover, AHI4 induced drought stress tolerance in radish (Raphanus sativus) seedlings (Araki et al 2006). These results strongly suggested that AHI4 is an effective ABA catabolic inhibitor, although this report did not show whether AHI4 increased the endogenous amount of ABA.…”
Section: Aba Catabolic Inhibitorsmentioning
confidence: 95%
“…13,14 To chemically control ABA 8'-hydroxylation in plants, we are developing ABA analogues that function as competitive inhibitors against ABA 8'-hydroxylase. [15][16][17] AHI4, which was developed in a previous study, requires a very high concentration (> 400 μM) to confer drought tolerance by its exogenous application. 17 On the other hand, uniconazole (UNI), which is a well-known plant retardant developed in the 1980s, 18,19 strongly inhibits ABA 8'-hydroxylase both in vitro and in vivo.…”
mentioning
confidence: 99%
“…[15][16][17] AHI4, which was developed in a previous study, requires a very high concentration (> 400 μM) to confer drought tolerance by its exogenous application. 17 On the other hand, uniconazole (UNI), which is a well-known plant retardant developed in the 1980s, 18,19 strongly inhibits ABA 8'-hydroxylase both in vitro and in vivo. [20][21][22] Saito et al reported that UNI induces drought tolerance in Arabidopsis plants at 50 μM.…”
mentioning
confidence: 99%